Soil-Transmitted Helminth Infections, Anemia, and Undernutrition Among School-Children in An Elementary School in North Jakarta, Indonesia - Sari, Monica Puspa; Nathasaria, Tabita; Majawati, Esther Sri; Pangaribuan, Helena Ullyartha (Majalah Kedokteran Bandung, 2020)
The strategy to control soil-transmitted helminth (STH) is through periodic deworming to eliminate infective worms among children. Helminthiasis is known to impair the nutrition and physical status of infected children. This study aimed to determine the prevalence and relationship between nutritional status and infection among School-Age Children (SAC) following deworming campaigns in Public Elementary School 6 Cilincing, North Jakarta, Indonesia. This study was a cross-sectional analytical observation on 82 children sampled using the Kato Katz approach during the period of August and November 2019. Nutritional status was determined using the standardized AnthroPlus Software while the Kolmogorov Smirnov test was used to statistically analyze the data. A structured questionnaire was used to collect data on hygiene and deworming pill consumption. Results showed that 7.3% of 82 children were infected with at least one of the following STH parasites: Ascaris lumbricoides accounts (n=3, 3.7%), Trichuris trichiura (n=2, 2.4%), and Enterobius vermicularis (n=1, 1.2%). Anemia was defined as a hemoglobin concentration of <8-11.9 g/dL for the age group of 8-13 years old. Of all participants, 10 (12%) were anemic. The proportion of children representing mild and moderate anemia were 4% and 6%, respectively. The prevalence of infection was not associated with anemia and STH infection did not present significant association with undernutrition statusAlmost children practiced hand washing before eating (93.9%). About 96% of children had pit latrines and only 24 children (29.5%) took deworming pills in the last 6 months. Thus, routine anthelminthic treatment for school children in urban areas is necessary. Infeksi Cacing yang ditularkan melalui Tanah, Anemia dan Gizi Buruk pada Anak Sekolah Dasar di Jakarta Utara, Indonesia Strategi pengendalian cacingan melalui pemberian obat cacing  berkala untuk memberantas cacingan pada anak. Anak terinfeksi dapat mengalami gangguan gizi dan fisik. Penelitian bertujuan mengetahui prevalensi STH dan hubungan status gizi anak sekolah pasca kampanye pemberantasan cacing di SDN 6 Cilincing, Jakarta Utara. Observasional analitik dengan desain studi potong lintang digunakan dalam sampel kato-katz dari 82 anak sekolah. Penelitian dilakukan dari Agustus-November 2019. Status gizi ditentukan menggunakan software AnthroPlus. Uji Kolmogorov smirnov untuk menganalisis data. Hasil penelitian menunjukkan  7,3% dari 82 anak terinfeksi setidaknya satu parasit STH. Parasit yang teridentifikasi, Ascaris lumbricoides sebanyak 3 (3,7%). Trichuris trichiura 2 (2.4%) diklasifikasikan infeksi ringan dan Enterobius vermicularis 1 (1,2%). Anemia didefinisikan bila konsentrasi Hb <8-11,9 g/dL untuk anak 8-13 tahun. Secara total, 10 (12%) anak anemia. Proporsi anak mewakili anemia ringan dan sedang masing-masing adalah 4%, dan 6%. Prevalensi infeksi tidak berhubungan dengan anemia. Anak positif STH tidak menunjukkan hubungan yang signifikan dengan kekurangan gizi pada anak. Pengumpulan data kuesioner dilakukan menggunakan kuesioner terstruktur. Hampir semua anak mempraktikkan kebersihan tangan yang benar, mencuci tangan sebelum makan (93,9%). Memiliki jamban 96% dan hanya 24 anak (29,5%) minum obat cacing 6 bulan terakhir. Hasil ini mendukung antihelmintik rutin pada anak sekolah di daerah perkotaan.